Estudo do processo de adsorção do ácido 2,4-diclorofenoxiacético (2,4 - d) pelo hidróxido duplo lamelar [Ni-Al-NO3] em coluna de leito fixo - Rosa, Naila Gleycy Collins (2023)
2,4-dichlorophenoxyacetic acid (2,4-D) is a herbicide, commonly used in agriculture, and one of the most commercialized in Brazil. However, the growing concern with environmental pollution has justified the need for development of technologies for pollutant removal. The aim of this work was to evaluate the adsorption efficiency of the herbicide 2,4-D by lamellar double hydroxides [Ni-Al-NO3] synthesized by coprecipitation method at pH 8.0± 0.5. Structural characterization of the adsorbent was carried out by X-ray diffraction (XRD), morphological characterization by scanning electron microscopy (SEM), thermal characterization by thermogravimetric analysis (TGA) and the specific surface area was determined by Brunauer-Emmett-Teller (B.E.T) method. XRD for HDL [Ni-Al-NO3] showed well-defined diffraction peaks, structure similar to hydrotalcite. In SEM images of the HDL, the presence of aggregated particles of asymmetric sizes with rounded edges and a porous morphology was observed. The B.E.T. showed a pore volume of 0.118 cm3 g-1 and a V-type isotherm. The adsorption experiments were performed with a 0.5 mmol L-1 herbicide solution at pH 3.5 in a fixed bed column at 21 oC, with only HDL [Ni-Al-NO3], and for comparison purposes a column containing active carbon (AC) and HDL [Ni-Al-NO3] + AC was also used. The HDL showed a higher adsorptive capacity (24.40 mg of adsorbate/g of adsorbent after 36 min) than that obtained by C.A. (18.86 mg of adsorbate g-1 of adsorbent after 30 min) and for C.A. + HDL (22.0 mg of adsorbate/g of adsorbent after 30 min). The adsorption kinetic experimental data for 2,4-D best fitted the pseudo-second order model. The adsorption process was best described by the Freundlich isotherm describing a physical interaction between the adsorbate and the adsorbent, values of 1/n in the range of 0 to 1, suggesting that adsorption on HDL is favorable and n>1, indicating the presence of energetically heterogeneous adsorbent sites. The thermodynamic parameters obtained indicated exothermic, spontaneous adsorption with decreasing degrees of freedom among the adsorbed species on the HDL surface. From the results of the fixed bed adsorption column parameters, it was concluded that HDL [Ni-Al-NO3] is a promising material as an adsorbent of the herbicide 2,4-D in contaminated water.